Coverings versus entourages - Collins, P; Morita, K (Elsevier, 1998)
The paper demonstrates the ‘equivalence’ of the Arhangel'skii-Stone, Collins-Roscoe and Frink Metrisation Theorems to the Morita ‘Double-Star’ Metrisation Theorem, and gives a range of uniform concepts generated by entourages and charaterising a variety of generalised metric properties.